2012
DOI: 10.2478/s13386-012-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Climate influence on radial increment of oak (Quercus SP.) in central Poland

Abstract: Abstract:The study investigates the influence of climate conditions on radial increment of oak, with special concern to the situations when analysed trees formed conspicuously wider or narrower treerings. The research material was collected in four locations in central Poland within natural range of pedunculate and sessile oaks. The elaborated residual chronologies were correlated with CRUTS 2.1 climate data. The analyses included thermal and pluvial conditions spanning from April of the year prior to ring for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Some of the characteristics also manifested significant correlations in July, August, and September ( Table 3). The significant positive effect of precipitation in May and June has also been proven by a number of European dendroclimatological and xylogenetic studies dealing with the sessile oak in France (Becker et al, 1994;Lebourgeois et al, 2004;Mérian et al, 2011;Michelot et al, 2012), Romania (Popa et al, 2013), Germany (Friedrichs et al, 2009), Slovakia (Petráš andMecko, 2011), Poland (Cedro, 2007;Bronisz et al, 2012), and Moravia, Czech Republic (Doležal et al, 2010). The negative effect of June (or July) temperatures has also been demonstrated repeatedly (Doležal et al, 2010;Mérian et al, 2011;Petráš and Mecko, 2011;Michelot et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the characteristics also manifested significant correlations in July, August, and September ( Table 3). The significant positive effect of precipitation in May and June has also been proven by a number of European dendroclimatological and xylogenetic studies dealing with the sessile oak in France (Becker et al, 1994;Lebourgeois et al, 2004;Mérian et al, 2011;Michelot et al, 2012), Romania (Popa et al, 2013), Germany (Friedrichs et al, 2009), Slovakia (Petráš andMecko, 2011), Poland (Cedro, 2007;Bronisz et al, 2012), and Moravia, Czech Republic (Doležal et al, 2010). The negative effect of June (or July) temperatures has also been demonstrated repeatedly (Doležal et al, 2010;Mérian et al, 2011;Petráš and Mecko, 2011;Michelot et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the effects of climate, including variations in mean temperature and total precipitation, on oak radial increment has recently been the subject of many European studies (Lebourgeois et al, 2004;Friedrichs et al, 2009;Tegel et al, 2010;Mérian et al, 2011;Petráš and Mecko, 2011;Bronisz et al, 2012). However, assessments of the relationship between crown condition and radial increment currently remain underrepresented (e.g., Drobyshev et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Also, farther east in the middle Volga region in Russia, a positive growth influence of spring-summer precipitation has been observed (Askeyev et al, 2005). According to Cedro (2007) as well as Bronisz et al (2012) oak growth in Poland is dominated by summer precipitation while high temperature has negative influence. Poor oak increment is mainly ascribed to the water deficit during the early summer in the Czech Republic (Doležal et al, 2010) and in Germany (Friedrichs et al, 2009; Scharn- weber et al, 2011;Zang et al, 2012).…”
Section: Summer Precipitation Signalmentioning
confidence: 91%
“…The time interval of 1886-1984 has been split (1886-1936, 1936-1984) and applied to the cross calibration-validation procedure where one set of predictor and predictant data, called the dependent set (half of time interval), is used to estimate the coefficients of the calibration model, while the remaining data, called independent data, is used to validation of the calibration model. The model, after the positive cross calibration-validation procedure, is once again calibrated from the whole time interval and the obtained new model coefficient is used to reconstruct the past climate changes from past variations in tree-ring growths (Cook and Kairiukstis 1990;Bradley 1999).…”
Section: Calibration and Verification Proceduresmentioning
confidence: 99%
“…Many authors found that the radial growth of pines and oaks, the most important forest tree species, growing outside the mountain areas in Poland, is mainly limited by the pre-growth season temperature (e.g., Wazny and Eckstein 1991;Zielski 1997;Cedro 2004Cedro , 2007SzychowskaKrąpiec 2010;Bronisz et al 2012;Koprowski et al 2012;Muter 2012). For both these taxons cold and frosty winters, low temperatures in early spring and dry summers are disadvantageous (in particular, all of these factors acting together) (Feliksik and Wilczyński 1998;Wilczyński 1999;Cedro 2007;Szychowska-Krąpiec 2010;Bronisz et al 2012). Although the period of cambial activity of pine begins in early May and lasts until the end of September, the annual growth of wood is also affected by climatic conditions in winter preceding the growth season (Ermich 1959).…”
Section: Introductionmentioning
confidence: 99%